Perkembangan dan tren penelitian dimasa depan dengan kata kunci supervisi pendidikan: analisis menggunakan bibiliometrik - Syafaruddin Syafaruddin; Alwizar Alwizar; Nurahasnawati Nurahasnawati; Hakmi Wahyudi; Darmawati Darmawati; M. Fahli Zatrahadi; Istiqomah Istiqomah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
In the context of global educational supervision, it is vital that we keep up with the latest research and development in this field. This new research and technology can be used to improve the way education is supervised around the world and to make education better overall. The goal of this study is to look at how research on the subject of educational supervision has grown over time. Data were obtained from 1939 to 2022 with 175 publications. In this study, there was no reason to limit the ability to comprehensively understand the various forms of data so that more data could be obtained. Scopus data was utilized in the analysis of this study. Later analysis of the study utilized help from openrefine, vosviewer, and Rstudio software. The results of the study explain that supervision education research is conducted in the fields of health, school education, and psychology. The most active authors in publishing articles on educational supervision are Zepeda SJ, but in more situations, they are Alfian, Arifin I, Black D, Dewhurst G, Imron A, Syafiq Humaisi M, Wiyono BB, and Zepeda SJ, respectively. Research on this theme is being done more in the United Kingdom, followed by the United States. Currently, the keyword education supervision in database scopus is still prominent and indicates that this research is still in demand by researchers. But in the future, research related to the theme of supervision education is better directed at the following themes: human, medical education, child, adolescent, teaching, career, normal human, primary medical care, health care, infants and newborns, child preschool, professional competence, and medical specialists.